Mechanical Response of an Epithelial Island Subject to Uniaxial Stretch on a Hybrid Silicone Substrate - Bashirzadeh, Yashar; Dumbali, Sandeep; Qian, Shizhi; Maruthamuthu, Venkat (Cellular and molecular bioengineering, 2019)
Introduction The mechanical response of large multi-cellular collectives to external stretch has remained largely unexplored, despite its relevance to normal function and to external challenges faced by some tissues. Here, we introduced a simple hybrid silicone substrate to enable external stretch while providing a physiologically relevant physical micro-environment for cells. Methods We micropatterned epithelial islands on the substrate using a stencil to allow for a circular island shape without restraining island edges. We then used traction force microscopy to determine the strain energy and the inter-cellular sheet tension within the island as a function of time after stretch. Results While the strain energy stored in the substrate for unstretched cell islands stayed constant over time, a uniaxial 10% stretch resulted in an abrupt increase, followed by sustained increase in the strain energy of the islands over tens of minutes, indicating slower dynamics than for single cells reported previously. The sheet tension at the island mid-line perpendicular to the stretch direction also more than doubled compared to unstretched islands. Interestingly, the sheet tension at the island mid-line parallel to the stretch direction also reached similar levels over tens of minutes indicating the tendency of the island to homogenize its internal stress. Conclusions We found that the sheet tension within large epithelial islands depends on the midline direction relative to that of the stretch initially, but not at longer times. We suggest that the hybrid silicone substrate provides an accessible substrate for studying the mechanobiology of large epithelial cell islands.